2023
DOI: 10.3390/su15043530
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Win-Win Solution for Dietary Health and Carbon Reduction—Evidence from the Yangtze River Delta in China

Abstract: Considering the contradiction between the need to change the food consumption structure of Chinese residents and the constraints of resources and the environment, as well as the changes in the consumption structure of Chinese residents in the Yangtze River Delta, we explore the path to achieve environmental sustainability while maintaining residents’ dietary health. Based on 1995–2019 Yangtze River Delta food consumption data, this paper uses the two-stage Engel–QUAIDS model to conduct an empirical analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Chen et al (2023) found that social factors, such as the industrial structure, human capital, and economic base of the Yangtze River Economic Belt, significantly affect the synergy between pollution and carbon emission reduction. Guo et al (2022) and Jian et al (2023) had similar findings.…”
Section: Introductionmentioning
confidence: 57%
“…Chen et al (2023) found that social factors, such as the industrial structure, human capital, and economic base of the Yangtze River Economic Belt, significantly affect the synergy between pollution and carbon emission reduction. Guo et al (2022) and Jian et al (2023) had similar findings.…”
Section: Introductionmentioning
confidence: 57%
“…With the acceleration of urbanisation, China's food consumption structure has been upgraded. Chinese have a growing demand for agricultural products, particularly meat and dairy products [ 14 ]. According to statistics from the Food and Agriculture Organization (FAO) of the United Nations, the largest source of greenhouse gas emissions in agriculture comes from methane produced during livestock digestion, with enteric fermentation, manure, and manure management accounting for 72% of agricultural carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…As such, establishing a dietary pattern and medical inputs strategy that caters to the holistic health requirements of the nation is a public health priority 16 . While earlier studies have focused predominantly on the national dietary structure regarding food security, soil and water environment, carbon emissions, and nutritional diseases, it is imperative to acknowledge that medical expenditures constitute a significant aspect of the overall dietary system that cannot be overlooked 11,[17][18][19][20][21][22][23][24][25][26][27][28][29] . Most studies have prioritized investigating the correlation between medical expenditures and national health 30 , frequently relying on proxy variables, such as life expectancy and mortality rates to evaluate the productive performance of national health [31][32][33][34][35] .…”
mentioning
confidence: 99%